2005
DOI: 10.1111/j.1469-7580.2005.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensory innervation in rat tibia: co‐localization of CGRP and substance P with growth‐associated protein 43 (GAP‐43)

Abstract: The development of sensory innervation in long bones was investigated in rat tibia in fetuses on gestational days (GD) 16 -21 and in neonates and juvenile individuals on postnatal days (PD) 1-28. A double immunostaining method was applied to study the co-localization of the neuronal growth marker growth-associated protein 43 (GAP-43) and the pan-neuronal marker protein gene product 9.5 (PGP 9.5) as well as that of two sensory fibre-associated neuropeptides, calcitonin gene-related peptide (CGRP) and substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 37 publications
(84 reference statements)
3
36
0
Order By: Relevance
“…GAP-43 is a presynaptic protein implicated in axonal growth, neuronal differentiation, plasticity, and regeneration (Chakravarthy et al 2008). GAP-43 is an axonal regeneration marker (Murata et al 2006;Aoki et al 2007;Kimura et al 2007;Anand et al 2008) and a neuronal growth marker (Gajda et al 2005;Mechsner et al 2007;Zinck et al 2007). It has been reported that local h Quantitative analysis of the ratio of apoptotic cells at different experimental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…GAP-43 is a presynaptic protein implicated in axonal growth, neuronal differentiation, plasticity, and regeneration (Chakravarthy et al 2008). GAP-43 is an axonal regeneration marker (Murata et al 2006;Aoki et al 2007;Kimura et al 2007;Anand et al 2008) and a neuronal growth marker (Gajda et al 2005;Mechsner et al 2007;Zinck et al 2007). It has been reported that local h Quantitative analysis of the ratio of apoptotic cells at different experimental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…It is now recognized that the regulation of bone involves other systems within the organism, including the CNS. It has been known for long time that bone is an innervated tissue containing both efferent and afferent fibers in bone marrow and the periosteum (1). However, the first clear evidence that central signaling affects bone mass was the finding that leptin-deficient mice, despite their hypogonadism, had high bone mass, and that this phenotype was reversed by intracerebroventricular injections of leptin (2).…”
mentioning
confidence: 99%
“…Gajda et al [128] investigated the development of sensory innervation in long bones, see Figure 1.18. Their model was rat tibia in fetuses and in juvenile individuals on postnatal days.…”
Section: Anatomy Of Bone Innervationmentioning
confidence: 99%